Writing society: politics and history in the work of D.H. Lawrence - Simmonds, Roger (2004)
This thesis is a cultural materialist exploration of the trans-generic work of D. H. Lawrence. Combining formalist analyses with this historical approach, I provide perspectives on Lawrence which attend to the particularity of his texts' form while revealing their constitution as historical and material products. The consequence is neither a "radicalized" Lawrence nor a right-wing caricature of him, but a politically hybrid Lawrence whose texts are sites of struggle with the socio-historical contradictions of modernity. In chapter 1, I show how Lawrence can critique bourgeois culture and its material foundations more profoundly than has been assumed. Pansies, whose dialogical poetics undermines conventional literary genres and assaults a bourgeois "literature" which suppresses its materiality, is read as a critique of its own conditions of production. In chapter 2, I illustrate how Lawrence's post-war work is more embattled than• is usually realised, in its intense exploration of the contradictions of liberal capitalism; the notion of Lawrence's post-war texts as largely monologic and reactionary is radically undermined. In chapter 3, I argue that Lawrence's life as an exile does not signify, as it is normally understood to, a sustained hostility to England and nation-ness. Rather, Lawrence's articles on Englishness offer an abstract, bourgeois myth of England which occludes the conflicts of class and gender. Finally, in chapter 4, I illuminate the darker cultural roots of Lawrence's unconscious, which is commonly perceived as a liberatory force, opposing hegemonic cultural ideologies. While Lawrence critiques the hypocrisy and repression of modern democratic idealism, his positing of an extra-cultural unconscious is haunted by an intensified version of the very cultural repression he assaults.